Internet addiction among engineering students in Belagavi city: cross sectional study - Kamate, Ravikiran; Baliga, Sulakshna; Mallapur, M. D. (International Journal Of Community Medicine And Public Health, 2019)
Background: Internet addiction is not clinical diagnosis, but a potentially pathological behavioral pattern with symptoms: a loss of control over the behavior, preoccupation with the Internet, using the Internet to modify mood, and withdrawal symptoms. Easy access and low cost of Internet packs- are main cause of development of increased internet use in India. Internet addiction – factors like gender, environmental factors, socioeconomic status, etc. have effect on internet use. Methods: Cross-sectional study conducted during January 2016 to February 2016. Data was collected among 500 engineering students of four engineering colleges of Belagavi city using young's questionnaire. Analysis was performed using SPS 20. Chi-square applied as statistical test of significance for the association between age, sex, residence, SES and schooling. P<0.01 was considered to be statistically significant. Results: The present study revealed that 16.2 and 6.2% of participants had moderate and severe form of internet addiction respectively. With increase in age prevalence of addiction increased. Internet addiction was more among Males when compared to females. Addiction was seen more in students whose both parents were working. Conclusions: Internet addiction is an emerging form of addiction among students with males more than females mostly among engineering students who are dependent on internet for their work, carrier and completion of course Hence it's time to develop comprehensive intervention approach to promote healthy and safe internet use from family, college and peers.